Hormonal profile and Agnor values in pituitary adenomas - (:unkn) unknown (My University, 2001)
Nucleolar organizer regions (NORs) are chromosomal segments in which ribosomal RNA is encoded. The AgNOR technique, which reveals these regions, has rarely been used in diagnosis and preceding the prognosis of pituitary adenoma. The purpose of this study was to evaluate the correlation of hormonal profile with the AgNOR counts, and the correlation of recurrence with the AgNOR counts and to determine the concordance between the evaluations of two different observers. This study included 33 patients with pituitary adenoma. The slides were stained with hematoxylin and eosin, silver colloid method for NORs and immunohistochemistry for the hormone expressions. Consistency was strong among the two pathologists (for hormonal profiling, the kappa test was used and p<0. 001; for AgNOR count, the intraclass correlation coefficient was 0. 83). There was no significant relationship between mean AgNOR counts and hormone expression (p>0. 05). In addition, we found no difference between recurrent patients and non-recurrent ones in terms of mean AgNOR numbers (p>0. 05). However, in recurrent patients, nucleolar silver staining was more frequently detected as clusters of AgNORs.
Keywords: AgNOR; Immunohistochemistry; Pituitary adenoma; Recurrence